Method for tempering glass through low-temperature ion exchange

Through the two-step ion exchange strengthening method, the first and second ion exchange strengthening is carried out using lithium salt and potassium salt respectively, which solves the problems of low-temperature ion exchange strengthening glass surface low-stress and severe warping, achieving higher glass reinforcement effect.

CN119409428APending Publication Date: 2025-02-11QINHUANGDAO GLASS IND RES & DESIGN INST
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411771870.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing low-temperature ion exchange method reinforced glass has low surface stress and severe warping, making it difficult to meet the practical application needs.

Method used

A two-step ion exchange enhancement method was adopted, firstly using lithium salt for the first ion exchange enhancement, followed by potassium salt for the second ion exchange enhancement, and the temperature was controlled between 250 and 400℃.

Benefits of technology

It significantly improves the surface stress of the glass, reduces warping, and meets the performance needs of practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409428A_ABST
    Figure CN119409428A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of glass, in particular to a method for strengthening glass through low-temperature ion exchange, which comprises the following steps: carrying out first ion exchange strengthening treatment on glass to be treated by adopting first molten salt to obtain primary strengthened glass; carrying out secondary ion exchange strengthening treatment on the primary strengthened glass by adopting second fused salt to obtain the low-temperature ion exchange strengthened glass, wherein the first molten salt comprises a lithium salt, the second molten salt comprises a potassium salt, the temperature range of the first ion exchange strengthening treatment and the second ion exchange strengthening treatment is 250-400 DEG C, and the ion exchange temperature requirement can be met. The two-step strengthening is adopted at low temperature to gradually enhance the surface stress of the glass, so that the bending deformation of the glass caused by sudden enhancement of the surface stress of the strengthened glass is avoided, and the phenomenon of warping of the edge of the glass is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass, and in particular to a method for strengthening low-temperature ion exchange glass. Background Art

[0002] Insulating glass is a high-performance sound-insulating and heat-insulating glass made by bonding two (or three or more) glass sheets to an aluminum alloy frame containing a desiccant using a high-strength and high-airtightness composite adhesive. Its various properties are significantly better than those of ordinary double-layer glass. However, as a brittle material, glass sheets are prone to cracking and breaking during use. In order to ensure the safety factor and service life of insulating glass, the glass sheets used to make insulating glass need to have a certain load-bearing capacity.

[0003] Ion exchange (also known as chemical strengthening) is the main technical approach to improve the mechanical properties of glass. According to the type of exchanged ions and the temperature of ion exchange, it can be divided into two types of ion exchange methods: high-temperature type above the glass transition point and low-temperature type below the glass transition point. Among them, the high-temperature ion exchange method usually refers to the low expansion coefficient microcrystals produced on the glass surface by ion exchange. Since its expansion coefficient is smaller than that of the internal expansion coefficient of the glass, compressive stress is generated after cooling to meet the requirements of glass strengthening. This method is also called surface crystallization method or expansion difference method, but the processing temperature of this method is too high, the glass is easy to deform, and it has little practical significance; the low-temperature ion exchange method usually refers to the glass transition point (T g ) below, large ions are exchanged for small ions, such as K + Ions to replace Na in glass + Ions, which in turn "crowd" and expand the glass surface, generate compressive stress, and strengthen the glass. Low-temperature ion exchange methods are more economical due to their low processing temperature and are widely used in actual production. However, the glass obtained by strengthening treatment using the existing low-temperature ion exchange method has the defects of low surface stress and severe warping, which makes it difficult to meet the needs of actual applications. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of low surface stress and severe warping of glass obtained by strengthening treatment by the existing low-temperature ion exchange method, thereby providing a method for solving the above problems by low-temperature ion exchange strengthening of glass.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A method for strengthening low-temperature ion exchange glass comprises: using a first molten salt to perform a first ion exchange strengthening treatment on a glass to be treated to obtain a first strengthened glass; using a second molten salt to perform a second ion exchange strengthening treatment on the first strengthened glass to obtain the low-temperature ion exchange strengthened glass; wherein the first molten salt contains a lithium salt, the second molten salt contains a potassium salt, and the temperature range of the first ion exchange strengthening treatment and the second strengthening treatment is 250-400°C.

[0007] Preferably, the lithium salt is lithium nitrate;

[0008] And / or, the potassium salt is potassium nitrate.

[0009] Preferably, the first molten salt further contains sodium salt;

[0010] And / or, the second molten salt further contains sodium salt.

[0011] Preferably, the molar ratio of lithium element to sodium element in the first molten salt is (1-2):1;

[0012] And / or, the molar ratio of potassium element to sodium element in the second molten salt is (1-2):1;

[0013] And / or, the sodium salt is sodium nitrate.

[0014] Preferably, the total duration of the first ion exchange strengthening treatment and the second ion exchange strengthening treatment (the duration of the first ion exchange strengthening treatment + the duration of the second ion exchange strengthening treatment) is 5 to 15 minutes; optionally, the first ion exchange strengthening treatment is 5 to 10 minutes.

[0015] Preferably, the first molten salt and the second molten salt are processed by coating;

[0016] And / or, the first ion exchange strengthening treatment and the second ion exchange strengthening treatment are carried out in the annealing stage of the process of preparing the glass to be treated, and the residual heat of the annealing process is used to melt the ion exchange molten salt, and the annealing temperature range of the annealing furnace is 600-150° C.;

[0017] And / or, cooling and washing are further performed after the first ion exchange strengthening treatment and / or the second ion exchange strengthening treatment.

[0018] Preferably, the coating is in the form of spraying.

[0019] Preferably, in the first ion exchange strengthening treatment, the coating amount of lithium element in the first molten salt is 2 to 5 mol / m 2 ;

[0020] And / or, in the second ion exchange strengthening treatment, the coating amount of potassium element in the second molten salt is 2-5 mol / m 2 .

[0021] Preferably, in the first ion exchange strengthening treatment, the coating amount of the first molten salt on 78% to 84% of the central area of ​​the surface of the glass to be treated is 4 to 5 mol / m 2 , 4~5mol / m 2 The spraying pressure corresponding to the coating amount is 0.45-0.6MPa, the flow rate is 8-12mol / min, and the coating amount of the remaining edge area is 2-3.5mol / m 2 , 2~3.5mol / m 2 The spraying pressure corresponding to the coating amount is 0.4-0.5MPa, and the flow rate is 0.5-1.5mol / min;

[0022] And / or, in the second ion exchange strengthening treatment, the coating amount of the second molten salt on 78-90% of the central area of ​​the surface of the first strengthened glass is 4-5 mol / m 2 , 4~5mol / m 2 The spraying pressure corresponding to the coating amount is 0.45-0.6MPa, the flow rate is 8-12mol / min, and the coating amount of the remaining edge area is 2-3.5mol / m 2 , 2~3.5mol / m 2 The spraying pressure corresponding to the coating amount is 0.4-0.5 MPa, and the flow rate is 0.5-1.5 mol / min.

[0023] Preferably, the thickness of the glass to be processed is 1 to 3 mm.

[0024] The technical solution of the present invention has the following advantages:

[0025] 1. A method for strengthening low-temperature ion exchange glass, comprising: using a first molten salt to perform a first ion exchange strengthening treatment on the treated glass to obtain a first strengthened glass; using a second molten salt to perform a second ion exchange strengthening treatment on the first strengthened glass to obtain a low-temperature ion exchange strengthened glass; wherein the first molten salt contains a lithium salt, the second molten salt contains a potassium salt, and the temperature range of the first ion exchange strengthening treatment and the second strengthening treatment is 250 to 400°C. In view of the problems that the glass obtained by strengthening treatment using the existing low-temperature ion exchange method has low surface stress and severe warping, the present invention adopts a two-step strengthening technical concept at low temperature to increase the surface stress of the glass and improve the warping problem of the glass after strengthening treatment. Specifically, the present invention first uses Li with a small ion radius in the first molten salt to strengthen the glass. + With the Na on the glass surface + Ion replacement is performed to promote partial Li +The ions enter the gaps in the crystal structure of the glass surface, forming a crowding effect on the glass surface, which enhances the surface stress of the glass. + The molten salt is strengthened twice to make the K in the molten salt + With the small radius ion Na in the glass + , Li + Ion replacement occurs, further enhancing the surface stress of the glass. The surface stress of the glass after two-step strengthening can reach 85-153MPa. Based on the above technical concept, the present invention adopts a two-step strengthening method to gradually enhance the surface stress of the glass, thereby avoiding the sudden increase of the surface stress of the strengthened glass causing the glass to bend and deform, effectively improving the phenomenon of the warping of the glass edge, and the order of the two strengthenings cannot be changed. This is because K + The ion radius of the ion is large. If potassium salt is used in the first step of strengthening, it will cause excessive stress on the strengthened surface, causing the glass to bend. In addition, the strengthening treatment temperature must be controlled within the range of 250-400°C. If it is higher than 400°C, the ion exchange will be intense, the glass will be severely warped, and energy consumption and cost will increase; if it is lower than 250°C, the ion exchange will be slow, the strengthening degree will be low, and the surface stress of the produced glass will still be low, which is difficult to meet the actual application needs.

[0026] 2. In the method of low-temperature ion exchange tempered glass of the present invention, nitrate is used as an ion exchange strengthening agent. This is because nitrate has a low melting point, a low strengthening temperature, and ions are easily ionized and decomposed into monovalent cations and nitrate ions, saving energy consumption, thereby reducing processing costs. For example, the melting point of lithium nitrate is 264°C, the melting point of potassium nitrate is 337°C, and the melting point of sodium nitrate is 310°C. In addition, nitrate is soluble in water, and the glass after ion strengthening treatment only needs to be washed with deionized water to remove the surface molten salt residue, which is simple to operate and low in cost.

[0027] 3. In the method of low-temperature ion exchange tempered glass of the present invention, sodium salt is added during the tempering treatment to further avoid glass warping caused by excessive surface stress of the tempering. At the same time, the use of a mixed salt of potassium salt and sodium salt during the second tempering treatment can also achieve the effect of lowering the melting temperature of the molten salt and reduce energy consumption.

[0028] 4. In the method of low-temperature ion exchange strengthened glass of the present invention, currently glass strengthening adopts offline strengthening (that is, the glass is heated and strengthened after being formed and cooled), while the present invention chemically strengthens the glass during the annealing process (that is, online strengthening). The glass during the annealing process is still in an elastic state, which is easy to carry out ion exchange. At the same time, the heat in the annealing zone of the furnace can be used to melt the molten salt, without the need for additional heating, thereby reducing energy consumption.

[0029] 5. In the method for low-temperature ion exchange tempered glass of the present invention, ion exchange tempering treatment is carried out by molten salt coating, which greatly shortens the tempering treatment time to only a dozen minutes or even a few minutes, and the treatment efficiency is significantly improved; at the same time, shortening the tempering treatment time can also reduce the probability of glass warping and surface stress reduction caused by glass stress relaxation due to long-term heating.

[0030] 6. In the method for strengthening low-temperature ion exchange glass of the present invention, the present invention adopts a technical means of spraying less at the edge of the glass plate and more in the middle in the molten salt spraying setting. This is because compared with the center of the glass plate, the edge of the glass plate cools down faster, which will produce a certain stress, thereby causing the glass to warp. The use of the above-mentioned technical means can further improve the glass warping phenomenon. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 is a schematic diagram of ion exchange for preparing low-temperature ion exchange strengthened glass in Example 1 of the present invention;

[0033] Figure 2 1 is a schematic diagram of the structure of a spraying device for performing ion exchange strengthening treatment during the annealing process of the glass to be treated according to Embodiment 1 of the present invention;

[0034] Figure 3 It is a schematic diagram of the structure of testing the glass warpage in Test Example 1 of the present invention;

[0035] Explanation of the reference numerals: 1-glass to be treated, 2-first molten salt spraying area, 3-second molten salt spraying area, 4-molten salt spraying pipeline, 5-molten salt nozzle, h-arc height, L-chord length. DETAILED DESCRIPTION

[0036] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0037] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0038] The glass ribbons to be strengthened (500 cm in width and 2 mm in thickness) involved in the following examples and comparative examples are all prepared by the following steps: quartz sand, soda ash, lithium carbonate, aluminum oxide and other raw materials are mixed evenly and then put into a glass kiln, and melted at 1380°C to form molten glass liquid, and the molten glass liquid is annealed and cooled to form the glass ribbon to be strengthened. The annealing temperature range of the annealing kiln is 600-150°C; the glass ribbon components, in terms of mass percentage, include: 75% SiO2, 12% Na2O, 5% Li2O, 4% Al2O3, 2% B2O3, 1% MgO, and 1% CaO.

[0039] Example 1

[0040] This embodiment provides a method for low-temperature ion exchange tempered glass, and the specific steps are as follows:

[0041] 1) lithium nitrate and sodium nitrate are weighed and mixed in a molar ratio of 2:1, and melted by using the waste heat of the annealing furnace to obtain a mixed molten salt, and then the mixed molten salt is pumped into a molten salt spraying pipeline 4 with a molten salt nozzle 5, and the mixed molten salt is sprayed on the surface of a moving glass strip 1 to be strengthened at 250° C. in a first molten salt spraying area 2, and a strengthening treatment is performed for 2.5 minutes; wherein, the spraying amount of lithium element in the mixed molten salt on the edge areas with a width of 40 cm on both sides of the glass strip to be strengthened is 2 mol / m 2 The molten salt spraying pressure is 0.42MPa, the flow rate is 0.6mol / min, and the spraying amount in the remaining center width area of ​​420cm is 5mol / m 2 , the molten salt spraying pressure is 0.5MPa, and the flow rate is 11mol / min;

[0042] 2) Using the waste heat from the annealing furnace to melt potassium nitrate to obtain potassium nitrate molten salt, spray the potassium nitrate molten salt onto the glass surface at 250°C after the first strengthening treatment in step 1) in the second molten salt spraying area 3 for a second strengthening treatment for 2.5 minutes, and the potassium element in the potassium nitrate molten salt is sprayed in an amount of 2 mol / m2 on both sides of the edge area with a width of 25 cm on the glass strip to be strengthened. 2 The molten salt spraying pressure is 0.4MPa, the flow rate is 0.5mol / min, and the spraying amount in the remaining center width area of ​​450cm is 5mol / m 2The molten salt spraying pressure is 0.48MPa, the flow rate is 11.25mol / min, and finally the glass ribbon is naturally cooled and washed with water to remove the surface molten salt; the schematic diagram of the ion exchange of the primary strengthening treatment and the secondary strengthening treatment is shown in Figure 1 As shown, the schematic diagram of the spraying device structure is as follows Figure 2 shown.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that the total duration of the first reinforcement treatment and the second reinforcement treatment is 10 minutes (the duration ratio of the first reinforcement to the second reinforcement is 1:1), and other conditions are the same as those in embodiment 1.

[0045] Example 3

[0046] The difference between this embodiment and embodiment 1 is that the total duration of the first reinforcement treatment and the second reinforcement treatment is 15 minutes (the duration ratio of the first reinforcement to the second reinforcement is 1:1), and other conditions are the same as those in embodiment 1.

[0047] Example 4

[0048] The difference between this embodiment and embodiment 1 is that the temperature of the primary strengthening treatment and the secondary strengthening treatment are both 300° C., the total strengthening treatment time is 5 minutes (the time ratio of the primary strengthening to the secondary strengthening is 1:1), and other conditions are the same as those in embodiment 1.

[0049] Example 5

[0050] The difference between this embodiment and embodiment 4 is that the total duration of the first reinforcement treatment and the second reinforcement treatment is 10 minutes (the duration ratio of the first reinforcement to the second reinforcement is 1:1), and other conditions are the same as those in embodiment 1.

[0051] Example 6

[0052] The difference between this embodiment and embodiment 4 is that the total duration of the first reinforcement treatment and the second reinforcement treatment is 15 minutes (the duration ratio of the first reinforcement to the second reinforcement is 1:1), and other conditions are the same as those in embodiment 1.

[0053] Example 7

[0054] The difference between this embodiment and embodiment 1 is that the temperature of the primary strengthening treatment and the secondary strengthening treatment are both 350° C., the total strengthening treatment time is 5 minutes (the time ratio of the primary strengthening to the secondary strengthening is 1:1), and other conditions are the same as those in embodiment 1.

[0055] Example 8

[0056] The difference between this embodiment and embodiment 7 is that the total duration of the first reinforcement treatment and the second reinforcement treatment is 10 minutes (the duration ratio of the first reinforcement to the second reinforcement is 1:1), and other conditions are the same as those in embodiment 1.

[0057] Example 9

[0058] The difference between this embodiment and embodiment 7 is that the total duration of the first reinforcement treatment and the second reinforcement treatment is 15 minutes (the duration ratio of the first reinforcement to the second reinforcement is 1:1), and other conditions are the same as those in embodiment 1.

[0059] Example 10

[0060] The difference between this embodiment and embodiment 1 is that the temperature of the primary strengthening treatment and the secondary strengthening treatment are both 380° C., the total strengthening treatment time is 5 minutes (the time ratio of the primary strengthening to the secondary strengthening is 1:1), and other conditions are the same as those in embodiment 1.

[0061] Embodiment 11

[0062] The difference between this embodiment and embodiment 10 is that the total duration of the first reinforcement treatment and the second reinforcement treatment is 10 minutes (the duration ratio of the first reinforcement to the second reinforcement is 1:1), and other conditions are the same as those in embodiment 1.

[0063] Example 12

[0064] The difference between this embodiment and embodiment 10 is that the total duration of the first reinforcement treatment and the second reinforcement treatment is 15 minutes (the duration ratio of the first reinforcement to the second reinforcement is 1:1), and other conditions are the same as those in embodiment 1.

[0065] Embodiment 13

[0066] The difference between this embodiment and embodiment 1 is that the edge spraying amount is 3.5 mol / m 2 , the intermediate spraying amount is 5mol / m 2 , other conditions are the same as in Example 1.

[0067] Embodiment 14

[0068] The difference between this embodiment and embodiment 1 is that the edge spraying amount is 3 mol / m 2 , the intermediate spraying amount is 3mol / m 2 , other conditions are the same as in Example 1.

[0069] Embodiment 15

[0070] The difference between this embodiment and embodiment 1 is that the edge spraying amount is 5 mol / m 2 , the intermediate spraying amount is 5mol / m 2, other conditions are the same as in Example 1.

[0071] Example 16

[0072] The difference between this embodiment and embodiment 1 is that the edge spraying amount is 5 mol / m 2 , the intermediate spraying amount is 3mol / m 2 , other conditions are the same as in Example 1.

[0073] Embodiment 17

[0074] The difference between this embodiment and embodiment 1 is that no sodium salt is added during the primary strengthening and the secondary strengthening, and other conditions are the same as those in embodiment 1.

[0075] Embodiment 18

[0076] The difference between this embodiment and embodiment 1 is that sodium salt is added during the primary strengthening (lithium: sodium molar ratio is 2:1) and the secondary strengthening (potassium: sodium molar ratio is 2:1), and other conditions are the same as those in embodiment 1.

[0077] Embodiment 19

[0078] The difference between this embodiment and embodiment 1 is that sodium salt is added in both the primary strengthening treatment and the secondary strengthening treatment, the molar ratio of lithium nitrate to sodium nitrate in the primary strengthening treatment is 1:1, the molar ratio of potassium nitrate to sodium nitrate in the secondary strengthening treatment is 1:1, the temperature of the primary strengthening treatment and the secondary strengthening treatment is 400°C, and the coating amount of each part of the glass surface in the primary strengthening treatment and the secondary strengthening treatment is 2 mol / m 2 , other conditions are the same as in Example 1.

[0079] Embodiment 20

[0080] The difference between this embodiment and embodiment 1 is that in the primary strengthening treatment and the secondary strengthening treatment, the spraying amount of the edge area with a width of 55 cm on both sides of the glass ribbon is 2 mol / m 2 The remaining center width is 390cm and the spraying amount is 4mol / m 2 , other conditions are the same as in Example 1.

[0081] Comparative Example 1

[0082] The difference between this comparative example and Example 1 is that the same amount of lithium nitrate, sodium nitrate and potassium nitrate are mixed and subjected to a one-step spraying strengthening treatment, and the other conditions are the same as those in Example 1.

[0083] Comparative Example 2

[0084] The difference between this comparative example and Example 1 is that potassium nitrate molten salt is first used for primary strengthening treatment, and then a mixed molten salt of lithium nitrate and sodium nitrate is used for secondary strengthening treatment. Other conditions are the same as those in Example 1.

[0085] Comparative Example 3

[0086] The difference between this comparative example and Example 1 is that the temperature of the primary strengthening treatment and the secondary strengthening treatment are both 200° C., and the other conditions are the same as those of Example 1.

[0087] Comparative Example 4

[0088] The difference between this comparative example and Example 2 is that the temperature of the primary strengthening treatment and the secondary strengthening treatment are both 450° C., and the other conditions are the same as those of Example 1.

[0089] Comparative Example 5

[0090] The difference between this comparative example and Example 3 is that the temperature of the primary strengthening treatment and the secondary strengthening treatment are both 450° C., and the other conditions are the same as those of Example 1.

[0091] Comparative Example 6

[0092] The difference between this comparative example and Example 2 is that the temperature of the primary strengthening treatment and the secondary strengthening treatment are both 470° C., and the other conditions are the same as those of Example 1.

[0093] Comparative Example 7

[0094] The difference between this comparative example and Example 3 is that the temperature of the primary strengthening treatment and the secondary strengthening treatment are both 470° C., and the other conditions are the same as those of Example 1.

[0095] Test Example 1

[0096] The glass after strengthening treatment in the above-mentioned embodiment and the comparative example was subjected to surface stress test and glass warpage test. The surface stress test method: the test was conducted according to the glass stress test method of GB / T18144-2008; the glass warpage test method: the strengthened glass was placed at room temperature (25°C) for 4 hours, and then the arc height h and the chord length L of the chemically strengthened glass were measured with a feeler gauge; the glass warpage was expressed as the percentage of the arc height to the chord length. The structural schematic diagram of the glass warpage test is shown in FIG. Figure 3 The surface stress and glass warpage test results are shown in Table 1 below.

[0097] Table 1

[0098]

[0099]

[0100] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for low temperature ion exchange tempered glass, characterized in that: include: A first ion exchange strengthening treatment is performed on the treated glass using a first molten salt to obtain a primary strengthened glass; a second ion exchange strengthening treatment is performed on the primary strengthened glass using a second molten salt to obtain a low-temperature ion exchange strengthened glass; wherein the first molten salt contains a lithium salt, the second molten salt contains a potassium salt, and the temperature range of the first ion exchange strengthening treatment and the second strengthening treatment is 250 to 400°C.

2. The method according to claim 1, characterized in that The lithium salt is lithium nitrate; And / or, the potassium salt is potassium nitrate.

3. The method according to claim 1 or 2, characterized in that: The first molten salt also contains sodium salt; And / or, the second molten salt further contains sodium salt.

4. The method according to claim 3, characterized in that The molar ratio of lithium element to sodium element in the first molten salt is (1-2):1; And / or, the molar ratio of potassium element to sodium element in the second molten salt is (1-2):1; And / or, the sodium salt is sodium nitrate.

5. The method according to any one of claims 1 to 4, characterized in that: The total duration of the first ion exchange strengthening treatment and the second ion exchange strengthening treatment is 5 to 15 minutes.

6. The method according to any one of claims 1 to 5, characterized in that: The first molten salt and the second molten salt are processed by coating; And / or, the first ion exchange strengthening treatment and the second ion exchange strengthening treatment are carried out in the annealing stage of the process of preparing the glass to be treated, and the residual heat of the annealing process is used to melt the ion exchange molten salt, and the annealing temperature range of the annealing furnace is 600-150° C.; And / or, the first ion exchange strengthening treatment and / or the second ion exchange strengthening treatment are further followed by cooling and cleaning.

7. The method according to claim 6, characterized in that The coating is in the form of spraying.

8. The method according to claim 6 or 7, characterized in that: In the first ion exchange strengthening treatment, the coating amount of lithium element in the first molten salt is 2-5 mol / m 2 ; And / or, in the second ion exchange strengthening treatment, the coating amount of potassium element in the second molten salt is 2-5 mol / m 2 .

9. The method according to claim 8, characterized in that In the first ion exchange strengthening treatment, the coating amount of the first molten salt on 78-84% of the central area of ​​the surface of the glass to be treated is 4-5 mol / m 2 The coating amount of the remaining edge area is 2 to 3.5 mol / m 2 ; And / or, in the second ion exchange strengthening treatment, the coating amount of the second molten salt on 78-90% of the central area of ​​the surface of the first strengthened glass is 4-5 mol / m 2 The coating amount of the remaining edge area is 2 to 3.5 mol / m 2 .

10. The method according to any one of claims 1 to 9, characterized in that: The thickness of the glass to be processed is 1 to 3 mm.

Citation Information

Cited By

  • Low-temperature ion exchange strengthening process method for high-strength glass

    CN121044817A

  • A low temperature ion exchange strengthening process for high strength glass

    CN121044817B